2022
DOI: 10.1108/bfj-05-2021-0463
|View full text |Cite
|
Sign up to set email alerts
|

The impact of front-of-the-packaging nutrition labelling warnings on consumer habits: a scoping review exploring the case of the Chilean Food Law

Abstract: PurposeThe purpose of this scoping review was to summarise the general results of the Chilean Food Law implementation to help to understand how this policy has changed consumer's behaviour.Design/methodology/approachPreferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews (PRISMA-ScR) guidelines were followed. Five databases were searched for studies published from January 2015 to February 2020 evaluating the Chilean population's perception, behaviour and purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…The labels continue to perform better in one dimension of decision making-the objective understanding-in 18 countries [141], in Netherlands [142], French adolescents [143], Chile [144] and, other studies, confirm that is associated to a reduction of consumed harmful products [144]. Conversely, other research discussed the effectiveness of bundled FoPL composed by Health Star Rating and Warning Labels [145] in a realworld selection task. As for Warning Labels, other authors [146] showed the higher utility attached by consumers that is associated to the willingness to pay higher prices for products with such labels.…”
Section: What's Next With the Most Recent Contributions?mentioning
confidence: 97%
“…The labels continue to perform better in one dimension of decision making-the objective understanding-in 18 countries [141], in Netherlands [142], French adolescents [143], Chile [144] and, other studies, confirm that is associated to a reduction of consumed harmful products [144]. Conversely, other research discussed the effectiveness of bundled FoPL composed by Health Star Rating and Warning Labels [145] in a realworld selection task. As for Warning Labels, other authors [146] showed the higher utility attached by consumers that is associated to the willingness to pay higher prices for products with such labels.…”
Section: What's Next With the Most Recent Contributions?mentioning
confidence: 97%
“…Business people must produce innovative bundling designs for their items to market. These allow the keeping and catching the new and existed customers, because packaging has superior influence and also helps in acquiring and retaining the new consumers for their new products Silva, Bento, and Guaraldo (2022) summarised the general results of the Chilean Food Law implementation to help to understand how this policy has changed consumer's behaviour. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews (PRISMA-ScR) guidelines were followed.…”
Section: Previous Studymentioning
confidence: 99%
“…A first classification of the labels differentiates them into non-interpretative and interpretative. Non-interpretative labels offer quantitative information on specific nutrients without any type of judgment, opinion, orientation or qualitative element to assist in the interpretation of the information (Da Silva et al, 2022). Interpretative labels provide an overall evaluation of the product healthiness, a compilation of information that can help consumer to evaluate food products effectively (Cecchini & Warin, 2016;Newman et al, 2018).…”
Section: Interpretative Labelling: Nutritional Claims and Nutri-scorementioning
confidence: 99%
“…Any case, labelling is an effective way to provide information to consumers about the food content and promote healthier food choices (Da Silva et al, 2022;Kumar & Kapoor, 2017;Sarda et al, 2020;Thaivalappil et al, 2019). For this reason, many countries use nutritional labelling, a type of behavioural intervention closes to nudges and far from coercion and prohibitions (Awasthi, 2021;Salnikova & Stantan, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation